Influence of micro arc oxidation on high temperature oxidation resistance of AlTiCrVZr refractory high entropy alloy. (August 2021) - Shi, Xiaoqian; Yang, Wei; Cheng, Zhaohui; Shao, Wenting; Xu, Dapeng; Zhang, Yong; Chen, Jian
Abstract: In order to inhibit the volatilization of V and improve the high temperature oxidation resistance of AlTiCrVZr refractory high entropy alloy, the micro arc oxidation (MAO) coatings were prepared on AlTiCrVZr high entropy alloy in three different electrolytes: (1) Na2 SiO3, (2) Na2 SiO3  + (NaPO3 )6  + NaOH, (3) Na2 SiO3  + (NaPO3 )6  + NaOH + Na2 B4 O7  + KF. The results showed that the MAO coating was relatively smooth and dense in Na2 SiO3  + (NaPO3 )6  + NaOH + Na2 B4 O7  + KF, which was better than the other two electrolytes. The MAO coating contained some oxides, such as Al2 O3, Cr2 O3, SiO2, ZrO2 and TiO2 . The high temperature oxidation resistance of MAO coated AlTiCrVZr was improved compared with the uncoated substrate. After oxidation for 5 h, the high temperature oxidation resistance of MAO coated AlTiCrVZr in Na2 SiO3  + (NaPO3 )6  + NaOH was the best. After oxidation for 20 h, the higher quality MAO coating formed in Na2 SiO3  + (NaPO3 )6  + NaOH+ Na2 B4 O7  + KF made the substrate present high temperature oxidation resistance. Highlights: MAO coating was prepared on AlTiCrVZr refractory high entropy alloy. The composition of electrolyte affected the microstructure of MAO coating. The high temperature oxidation resistance of MAO coated AlTiCrVZr refractory high entropy alloy was improved.